The Effect of Liquidity, Leverage, and Profitability on Financial Distress in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange - Baihaqi, Amar; Nurwati, Solikah; Rasyiana, Meisya; Anatasia, Neri; Yansyah, Dedi; Kuswanto, Ferdy; Pratama, Rionaldi Harya; Ali, Rahman (CV. Civiliza Publishing, 2025)
This study aims to analyze the influence of liquidity, leverage, and profitability on financial distress in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. Secondary data in the form of financial statements were processed using logistic regression methods to test the relationships between variables. The results show that liquidity and profitability have a significant negative effect on financial distress, meaning that higher liquidity and profitability reduce the risk of financial distress. Conversely, leverage has a significant positive effect, indicating that higher debt usage increases the risk of financial distress. These findings emphasize the importance of managing liquidity, capital structure, and profitability to maintain the company’s financial health. Therefore, company management needs to routinely evaluate and control these three aspects to minimize the risk of financial distress and ensure sustainable business continuity.